COPD: should diagnosis match physiology? - Studnicka, Michael (2020)
We are very grateful to Dr. Vanfleteren and colleagues for commenting on our data regarding overdiagnosed COPD2 and for putting this evidence into the framework of the current understanding of the disease. Based on the data presented on overdiagnosis, and on prior Burden of Obstructive Lung Disease (BOLD) observations on underdiagnosis,3 we truly believe that our worldwide community of pulmonary specialists could do much better in caring for this extremely prevalent and devastating disease. Overall, our data indicate that for one patient with a “matched” COPD diagnosis (ie, the presence of postbronchodilator airway obstruction and a positive recall of such a diagnosis), there is always another “mismatched,” false-positive patient with COPD. This patient possibly experiences all the untoward consequences, such as receiving expensive and possibly harmful medication, and missing chances for treatment of cardiac disease or asthma. On the contrary, for each “known” patient with COPD who has a poorly reversible airway obstruction, there are four to five other patients out there with yet undetected airways obstruction. Again, we are missing opportunities in these patients for smoking intervention, symptom relief, and prolongation of their lives.